1989
DOI: 10.1177/039139888901201004
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Need for Surgical Drainage of Pericardial Effusion in Patients with End-Stage Renal Disease

Abstract: The best approach to treatment of pericarditis accompanied by substantial pericardial effusion in end-stage renal disease (ESRD) patients is unknown. In a review of our experience, we found that ESRD patients with moderate-to-large or large (circa 250 mL or larger) pericardial effusions usually failed to improve with intensive dialysis and ultimately required surgical drainage of the effusion. Multivariate analysis revealed that effusion size was by far the most important factor predicting need for surgery. Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
21
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 17 publications
2
21
0
Order By: Relevance
“…Leehey et al [7] demonstrated that it is almost always necessary to resort to surgical intervention in dialysis pericarditis associ ated with large pericardial effusion (>250 ml). Hence, pericardiocentesis or surgical intervention should be per formed in the face of peritoneal dialysate in the abdomen.…”
Section: Discussionmentioning
confidence: 99%
“…Leehey et al [7] demonstrated that it is almost always necessary to resort to surgical intervention in dialysis pericarditis associ ated with large pericardial effusion (>250 ml). Hence, pericardiocentesis or surgical intervention should be per formed in the face of peritoneal dialysate in the abdomen.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiovascular disease included cerebrovascular disease, coronary arterial disease, congestive heart failure and peripheral vascular diseases [1] . Pericarditis was diagnosed clinically by the clinical symptoms/signs, electrocardiography changes and echocardiographic evidence of pericardial effusion [7][8][9][10][11][12][13] . Effusion magnitude was assessed either retrospectively, by the amount of fluid removed upon pericardiocentesis or surgery, or by echocardiography.…”
Section: Definitionsmentioning
confidence: 99%
“…Recommended therapies have included intensive hemodialysis or peritoneal dialysis, non-steroidal anti-inflammatories, glucocorticoids, pericardiocentesis, intra-pericardial installation of a long-acting non-absorbable glucocorticoid, pericardiostomy, pericardial window and pericardiectomy [6] . Intensive hemodialysis has been defined as daily hemodialysis for a period of 10-14 days [7][8][9][10][11][12][13] .…”
mentioning
confidence: 99%
See 2 more Smart Citations